특발망막전막에서 망막층간분리 유무에 따른 수술 전후 시력 및 해부학적 차이 - 이민수(Min Soo Lee), 방찬우(Chan Woo Bang), 송도윤(Do Yun Song), 방종욱(Jong Wook Bang), 전혜민(Hye Min Jeon), 윤희성(Hee Seong Yoon) (Daihan angwa haghoi jabji, 2019)
목적: 특발망막전막환자에서 수술 전 망막층간분리의 동반 유무에 따른 수술 전후 시력 및 망막층 구조의 차이에 대해서 알아보고자 하였다. 대상과 방법: 2015년 1월부터 2017년 12월까지 특발망막전막으로 진단받고 유리체절제술과 망막전막제거술 및 내경계막제거술을 시행 받은 환자 중 6개월 이상 경과 관찰이 가능하였던 연속된 환자를 대상으로 의무기록을 후향적으로 분석하였다. 술 전 빛간섭단층촬영으로 망막층간분리의 동반 유무에 따라 두 군으로 나누어 수술 전과 후 시력예후 및 망막 형태 변화를 비교 분석하였다. 결과: 전체 324안 중 망막층간분리를 동반한 1군은 61안, 망막층간분리를 동반하지 않은 2군은 263안이었으며, 술 전 및 최종 시력이 1군에서 유의하게 좋았다(p=0.01, p=0.02). 수술 전 망막내층 조직의 손상(disorganization of retinal inner layers, DRIL)은 1군에서 2군에 비해 유의하게 낮았다(p=0.01). 수술 전 중심황반두께는 두 군에 차이가 없었으나, 술 후 3개월, 6개월 및 최종에서 1군이 2군보다 유의하게 얇은 결과를 보였다. 수술 전 전체 망막두께에서 내층 및 외층이 차지하는 비율은 1군이 2군에 비해 유의하게 작았다. 결론: 특발망막전막에서 망막층간분리가 동반된 경우가 동반되지 않은 경우보다 수술 전 시력이 좋고 DRIL의 빈도가 낮았으며, 수술 후 중심황반두께가 얇고 시력예후도 우수하였다. 이는 망막층간분리가 망막전막의 지속적인 견인력에 대한 완충적 작용을 하여 망막층의 구조가 비교적 보존되었기 때문이라 생각한다. Purpose: To present differences in visual acuity and macular structure before and after surgery in patients with idiopathic epiretinal membrane (ERM) according to the presence of retinoschisis. Methods: This retrospective observational study included 324 eyes with idiopathic ERM, that underwent pars plana vitrectomy with ERM and internal limiting membrane peeling, and were followed for more than 6 months. Subjects were classified into two groups according to the presence of retinoschisis using preoperative optical coherence tomography (OCT; group 1, ERM with retinoschisis; group 2, ERM without retinoschisis). Preoperative and postoperative macular structure changes and surgical outcomes were compared. Results: Group 1 included 61 eyes, and group 2 included 263 eyes. Group 1 had a significantly higher preoperative and final postoperative best-corrected visual acuity compared with group 2 (p = 0.01, p = 0.02). Preoperative disorganization of retinal inner layers (DRIL) was significantly less in group 1 than group 2 (p = 0.01). Preoperative central macular thickness was not significantly different between the two groups. However, postoperative central macular thickness was significantly lower in group 1 than group 2 (p = 0.02, p = 0.01, p < 0.01). The ratio of the inner or outer layer in the total retinal thickness before surgery was significantly smaller in group 1 than in group 2 (p = 0.02, p = 0.04). Conclusions: Preoperative visual acuity was better and the occurrence of DRIL was less in idiopathic ERM with retinoschisis than without retinoschisis. Postoperative visual and structural outcome was better in idiopathic ERM with retinoschisis than without retinoschisis. Retinoschisis may have played a role in reducing the tractional force given to the inner and outer retina. KCI Citation Count: 0